State management of the educational services market in a multicultural region as a tool of provision of population’s high living standards - Sotnikova, O.A.; Shustova, E.P.; Nekhvyadovich, L.I.; Barabanova, M.I. (Public Administration and Regional Management in Russia, Contributions to Economics, PartF2, 173-183, 2020)
The purpose of the research is to determine scenarios and to develop a “road map” of implementing the optimal scenario of state management of the educational services market in multicultural regions of Russia in the interests of increasing the population’s living standards. It is substantiated that standardization (development and usage of common requirements to all universities) hinders the implementation of the potential of the educational services market in stimulating the increase of living standards in Russia’s regional economy. It is necessary to limit standardization in the Russia’s educational services market. The quality of provision of educational services (characteristics of the educational process) and their results (mastered competencies) should be standardized, but universities should have larger independence for their provision